Isolation and Identification of the Major Chemical Components in the Capitula of Matricaria chamomilla Grown in Khuzestan Province of Iran - Ashnagar, A.; Gharib Naseri, N.; Alavi, S.Y. (Asian Journal of Chemistry, 2010)
Matricaria chamomilla is an important medicinal plant known for its antiinflammatory, wound healing, spasmolitic and antiseptic actions since long time. In this research, the major chemical components of the volatile oil obtained by hydrodistillation from Matricaria chamomilla plant grown in the surrounding fields of the city of Dezful, North West of Khuzestan province of Iran, were separated and identified. First the family, genus and species of the plant were identified then the capitula of the plant were hydrodistilled by using Clevenger hydrodistillation apparatus and the volatile oil was collected. Separation of different components was achieved by successive TLC and column chromatography techniques. Three major components were separated, purified and identified as chamazulene, bisabolonoxid and bisabololoxid A. The chemical structures of the components were determined by their IR, 1H NMR and MS spectra.